(untitled) (Development Service Industry Management, 2024)
The article analyzes the development trends of rural green tourism, which are formed on the basis of scientific concepts, theories of tourism, spatial economy and economic-geographical foundations of nature management. It has been established that it is necessary to justify the most optimal approaches and organizational and economic tools for stimulating the subjects of rural green tourism, to develop rural green tourism at the micro and macro levels as efficiently as possible, without causing damage to the environment. The authors prove that the development of scientific theories and concepts of the formation of tourism originates from the end of the 19th and the beginning of the 20th centuries, it was caused by a sharp increase in the flow of vacationers. . In the 80s of the XX century. R. Butler developed this theory, which is related to the development of tourism not only in a particular area, but also within the entire region. The article substantiates that part of the theories and concepts that determine the features of the current state of rural green tourism are multifunctional. It is proven that they take into account not only the quality of service provision, but also the place and role of the tourist in causing damage to the environment.